The use of solvent relaxation technique to investigate headgroup hydration and protein binding of simple and mixed phosphatidylcholine/surfactant bilayer membranes - Rieber, K.; Sýkora, J.; Olżyńska, A.; Jelinek, R.; Cevc, G.; Hof, M. (Biochimica et biophysica acta, 2007)
The subject of this report was to investigate headgroup hydration and mobility of two types of mixed lipid vesicles, containing nonionic surfactants; straight chain Brij 98, and polysorbat Tween 80, with the same number of oxyethylene units as Brij, but attached via a sorbitan ring to oleic acid. We used the fluorescence solvent relaxation (SR) approach for the purpose and revealed differences between the two systems. Fluorescent solvent relaxation probes (Prodan, Laurdan, Patman) were found to be localized in mixed lipid vesicles similarly as in pure phospholipid bilayers. The SR parameters (i.e. dynamic Stokes shift, Δν, and the time course of the correlation function, C( t)) of such labels are in the same range in both kinds of systems. Each type of the tested surfactants has its own impact on water organization in the bilayer headgroup region probed by Patman. Brij 98 does not modify the solvation characteristics of the dye. In contrast, Tween 80 apparently dehydrates the headgroup and decreases its mobility. The SR data measured in lipid bilayers in presence of Interferon alfa-2b reveal that this protein, a candidate for non-invasive delivery, affects the bilayer in a different way than the peptide melittin. Interferon alfa-2b binds to mixed lipid bilayers peripherally, whereas melittin is deeply inserted into lipid membranes and affects their headgroup hydration and mobility measurably.